ANALISIS IMPLEMENTASI KEBIJAKAN PEMERINTAH KOTA BATU DALAM RANGKA PERLINDUNGAN DAN PELESTARIAN LINGKUNGAN HIDUP - Hamdan Akbar Safara; Choirul Saleh (Universitas Tribhuwana Tunggadewi, 2014)
The backrgound of research is from Parson in Hettne, the statement is transition between capitalist ecology with socialist ecology of the nature management by state. This suggests is country through the government is required to issue a public policy in the environmental field. In Indonesia, this is already happening, the exsistance of environmental regulations 4/1982 until now to the preservation and protection of environmental regulations 32/2009. Location of the study was conducted in the Batu City. Where the famous BatuCitywas a rich natural potential of mountains, and in the upper Brantas river basin have great influence on other parts of East Java region. This study have qualitative methods and use spiral analysize of Craswell. Produce the following findings: the environmental office more than likes to use regulations 32/2009, without base on local act 16/2011; actions carried out by the implementing actors, environmental management, supervision and control of the environment and the conservation and rehabilitation of the activities undertaken by the implementer of the environmental policy in Batu city.